Finding Guide to the Lupe Anguiano Collection (Box Listing) - Taylor, Evelyn
The Lupe Anguiano Collection Box Listing acts as a finding guide to the content of the collection. It provides detailed information of the content, such as titles to publications, authors, dates of publications, and helpful notes for identification.